BPQDs@Lipo-YSA Nanoplatform Triggers Mitophagy via PRKN/AKT1 to Drive Immunogenic Cell Death in Lung Adenocarcinoma - Li Ai; Zhijuan Liu; Ran Li; Ying Hu; Yongxia Li (Journal of Nanobiotechnology)
Abstract Background Lung adenocarcinoma, the most common type of non-small cell lung cancer (NSCLC), is a leading cause of cancer-related deaths globally due to its high incidence and treatment difficulty. Despite recent advancements in treatment methods, the prognosis for patients with advanced disease remains poor. Studies have shown that targeting mitophagy, the selective clearance of damaged mitochondria, can influence the sensitivity of cancer cells to treatment. Methods In this study, we designed and synthesized BPQDs@Lipo-YSA, a novel nanomaterial, aimed at specifically inducing mitophagy in lung adenocarcinoma cells. The nanomaterial was characterized using techniques such as transmission electron microscopy (TEM) and dynamic light scattering (DLS). The ability of BPQDs@Lipo-YSA to induce mitophagy was evaluated using Western blot, immunofluorescence, and flow cytometry. Additionally, in vitro and in vivo experiments were conducted to investigate the impact of BPQDs@Lipo-YSA on lung adenocarcinoma cells through the induction of immunogenic cell death (ICD). Results Experimental results showed that BPQDs@Lipo-YSA effectively induced mitophagy in lung adenocarcinoma cells by activating the PRKN/AKT1 pathway. More importantly, this induction of mitophagy significantly enhanced the cytotoxic effect on lung adenocarcinoma cells. In animal models, BPQDs@Lipo-YSA, by inducing ICD, markedly inhibited tumor growth and extended survival. Conclusions This study reveals the potential value of BPQDs@Lipo-YSA in lung adenocarcinoma treatment through the induction of mitophagy and ICD. This finding provides theoretical and technical support for the development of new therapeutic strategies for lung adenocarcinoma.